Electronic structure and x-ray magnetic circular dichroism in (Ge,Mn)Te diluted magnetic semiconductors - Antonov, V.N.; Shpak, A.P.; Bekenov, L.V.; Germash, L.P.; Yaresko, A.N. (Condensed Matter Physics, 2010)
The electronic structure of the (Ge,Mn)Te diluted magnetic semiconductors was investigated theoretically from first principles, using the fully relativistic Dirac linear muffin-tin orbital (LMTO) band structure method. The electronic structure is obtained with the local spin-density approximation (LSDA) as well as the LSDA+U method. The x-ray magnetic circular dichroism (XMCD) spectra of (Ge,Mn)Te DMSs at the Mn L2,3 edges are investigated theoretically from first principles. The origin of the XMCD spectra in the compound is examined. The calculated results are compared with available experimental data.